Description of malignancy rates in childhood- and adult-onset systemic lupus erythematous by proportional meta-analysis - Da Silva Aoki, Priscila Rodrigues [UNESP]; El Dib, Regina [UNESP]; Silva, Clovis Artur Almeida; Magalhaes, Claudia Saad [UNESP] (My University, 2017)
Objective: Describe malignancy rates in childhood onset and adult onset systemic lupus erythematous (SLE) by proportional meta-analysis. Methods: Two reviewers screened data from PubMed (1966-2015), EMBASE (1980-2015), and LILACS (1982-2015) for SLE-associated malignancy. Proportional meta-analysis with a random-effects model and 95% confidence intervals (CIs) were calculated according to SLE onset age andmean follow-up time. Statistical differencewas defined by 95% CI overlap. Results: Overall the malignancy rate reported in 30 case series with 96,578 subjects was 3.4% (95% CI, 0.0260-0.0442; I2 = 97.6%; P < 0.0001). The malignancy rate was 4.2% (95% CI, 0.0318-0.0531; I2 = 98%; P < 0.0001) in 25 adult-onset SLE series, compared with 0.5% (95% CI, 0.0003-0.0154; I2 = 62.6%; P = 0.03) in 5 childhood-onset SLE series. Overall, in those with less than 5 years' follow-up, the malignancy rate was 2.8% (95% CI, 0.013-0.047; I2 = 91%; P < 0.0001) compared with 3.6% (95% CI, 0.0226-0.0531; I2 = 98.3%; P < 0.0001) in those with more than 5 years' follow-up, which was not significant, with 95% CI overlap. Conclusions: The meta-analysis indicated lower malignancy rates in pediatric-onset SLE comparedwith adult-onset SLE, but accrued data from childhood-onset SLE are still needed.
Keywords: Cohort studies; Malignancy; Meta-analysis; Systemic lupus erythematosus